2013
DOI: 10.1097/mnm.0b013e32835aa7de
|View full text |Cite
|
Sign up to set email alerts
|

Is cerebral glucose metabolism affected by chemotherapy in patients with Hodgkin’s lymphoma?

Abstract: Our results support the conclusion of a very limited impact of ABVD chemotherapy on brain metabolism in patients with HD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 29 publications
3
30
2
Order By: Relevance
“…This was also notably shown for the inferior temporal/fusiform gyrus in a study using a VBM procedure [23] as well as for the dorsolateral prefrontal cortex in morphometric studies [28,29].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This was also notably shown for the inferior temporal/fusiform gyrus in a study using a VBM procedure [23] as well as for the dorsolateral prefrontal cortex in morphometric studies [28,29].…”
Section: Discussionmentioning
confidence: 87%
“…Certain studies have shown limited effects of cancer or of cancer treatments on brain metabolism [29,30], whereas others have shown more marked impacts [31][32][33]. To minimise this possibly confounding effect, we only selected patients: (1) with a minimal interval time of one month between the last chemotherapy or radiotherapy and the FDG-PET exam and (2) with normal neuropsychological tests including no symptom of depression at MINI test.…”
Section: Discussionmentioning
confidence: 99%
“…A dysfunction of this network could potentially explain the neurocognitive, behavioural and mood alterations found in some chemotreated cancer survivors [1-3]. Some authors hypothesized that prefrontal dysfunction could be linked to acute depression and posttraumatic stress in those patients that later normalize [44]. However, our patients were not depressed or anxious and were cognitively spared.…”
Section: Discussionmentioning
confidence: 95%
“…In the first such investigation (15), both 18 F-FDG and 15 O-water brain PET studies were performed on healthy control subjects and breast cancer patients previously treated or untreated by chemotherapy. Altered functioning of the prefrontal cortex and cerebellum in patients previously treated with adjuvant therapy, 5-10 y after their last dose of chemotherapy, was found.…”
Section: Crci: Neuroimagingmentioning
confidence: 99%